KEPEMIMPINAN DALAM MENGADOPSI INOVASI PENDIDIKAN TINGGI (Studi Kasus di IKIP PGRI Pontianak) - Rizky Amaliah; Aswandi Aswandi; Muhammad Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractUniversities must be able to survive and always develop so that leadership is needed inadopting innovations in this new era. The method of this research is a case studyresearch with qualitative approach. The partisipants of this research are one rector,five lecturers, two administration staffs and one college student of IKIP PGRI inPontianak. The technique of data collection is using observation, interview, documentand triangulation. The data analysis is using data collection, data reduction, datapresentation and verivication. The result of this research show that innovation adoptionis very well. The process of this innovation is applying the knowledge and technologywith a good communication with online and offline platform about one week to fourmonths in campus and two years for regional. The applying of leadership function inadopting innovation in IKIP PGRI Pontianak is effective. Supporting factors are: (1)Leader; (2) Subordinates; (3) Facilities and Infrastructure; (4) Rewards; (5)Accreditation; (6) Pandemic. The inhibiting factors are: (1) Network system; (2)Economic conditions; (3) Awareness for students, lecturers and employees to improvethemselves in adopting innovations; (3) Students' geographical conditions; (6) Limitedfunds.Keywords: The Leadership of Higher Education, Adopting Innovation.